2018
DOI: 10.4103/jovr.jovr_67_18
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulators of angiogenesis, ocular vascular homeostasis, and pathogenesis and treatment of exudative AMD

Abstract: Angiogenesis, the formation of new blood vessels from pre-existing capillaries, is very tightly regulated and normally does not occur except during developmental and reparative processes. This tight regulation is maintained by a balanced production of positive and negative regulators, and alterations under pathological conditions such as retinopathy of prematurity, diabetic retinopathy, and age-related macular degeneration can lead to growth of new and abnormal blood vessels. Although the role of proangiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 160 publications
(208 reference statements)
1
13
0
Order By: Relevance
“…It is well known that genomic methylation and dimethyl transferase activity are increased in tumour endothelial cells leading to angiogenesis and cell growth. This may mediated by inactivation of angiogenesis inhibitory genes such as; thrombospondin-1 (TSP1) and insulin-like growth factor binding protein-3 (IGFBP3) genes [43,45,46]. These observations are in agreement with previous studies, which reported that Methyltransferase inhibitors (5-AazD or zebularine) decreased vessel formation and inhibited angiogenesis in different tumour models [47].…”
Section: Discussionsupporting
confidence: 88%
“…It is well known that genomic methylation and dimethyl transferase activity are increased in tumour endothelial cells leading to angiogenesis and cell growth. This may mediated by inactivation of angiogenesis inhibitory genes such as; thrombospondin-1 (TSP1) and insulin-like growth factor binding protein-3 (IGFBP3) genes [43,45,46]. These observations are in agreement with previous studies, which reported that Methyltransferase inhibitors (5-AazD or zebularine) decreased vessel formation and inhibited angiogenesis in different tumour models [47].…”
Section: Discussionsupporting
confidence: 88%
“…Angiogenesis has a central role in the metabolism not only of normal tissue (during embryonic and fetal development, or wound healing processes), but also of tissues under pathological conditions, as in diabetic retinopathy, age-related macular degeneration, retinopathy of prematurity, or tumors [ 40 , 41 ]. It is relevant that hemodynamic forces are directly related to the regulation of angiogenesis [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant that hemodynamic forces are directly related to the regulation of angiogenesis [ 40 , 42 ]. Studies have demonstrated direct modulatory mechanical force effects of SS and cell stretch on adhesion, migration and morphogenesis of ECs [ 16 , 41 , 43 ]. Lesions in the vascular endothelium are common several processes such as inflammation and atherosclerosis where SS usually is low and/or is turbulent.…”
Section: Discussionmentioning
confidence: 99%
“…The stages of AMD include hard drusen, which is associated with localized malfunctions of the retinal pigment epithelium, soft drusen associated with diffuse dysfunction of the retinal pigment epithelium, and damage to photoreceptors [ 4 ]. In retinal degeneration, pigment epithelium-derived factor (PEDF), which is produced in retinal pigment epithelial (RPE) cells and maintains retinal homeostasis, is decreased, while the expression of vascular endothelial growth factor (VEGF) is increased [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%